2013
DOI: 10.1371/journal.pone.0063963
|View full text |Cite
|
Sign up to set email alerts
|

Increased Soluble CD4 in Serum of Rheumatoid Arthritis Patients Is Generated by Matrix Metalloproteinase (MMP)-Like Proteinases

Abstract: Higher soluble CD4 (sCD4) levels in serum have been detected in patients of infectious and chronic inflammatory diseases. However, how and why sCD4 is produced remains poorly understood. We establish sensitive ELISA and WB assays for sCD4 detection in conditioned medium of in vitro cell culture system and serum of chronic inflammatory patients. Serum samples from patients with systemic lupus erythematosus (SLE) (n = 79), rheumatoid arthritis (RA) (n = 59), ankylosing spondylitis (AS) (n = 25), gout (n = 31), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…MMP-3 has been implicated in joint and soft tissue destruction associated with these conditions, where it participates in the inflammatory response (10)(11)(12)(13). Synthesis of MMP-3 is tightly controlled in vivo (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-3 has been implicated in joint and soft tissue destruction associated with these conditions, where it participates in the inflammatory response (10)(11)(12)(13). Synthesis of MMP-3 is tightly controlled in vivo (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…Because matrix metalloproteinases (MMPs) are able to process virtually any component of the extracellular matrix (ECM), including collagen, laminin, and bioactive molecules, it has been suggested that MMPs may be important in inflammatory conditions, such as rheumatoid arthritis, metastasis and periodontitis (1,2). In particular, MMP-3 (known as stromelysin-1) has a wide substrate specificity and is capable of degrading many types of ECM proteins, such as collagen types II, III, IV, IX, and X, proteoglycans, fibronectin, laminin, and elastin (1,2), rendering MMP-3 crucial in connective tissue and bone remodeling (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, MMP-3 (known as stromelysin-1) has a wide substrate specificity and is capable of degrading many types of ECM proteins, such as collagen types II, III, IV, IX, and X, proteoglycans, fibronectin, laminin, and elastin (1,2), rendering MMP-3 crucial in connective tissue and bone remodeling (3,4). However, while it is intuitive that dental pulp destruction may be a function of MMPs, our previous study reported that MMP-3 actually accelerates wound healing following dental pulp injury (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-3 has been implicated in the joint and soft-tissue destruction associated with these conditions, where it participates in the inflammatory response (10)(11)(12)(13)(14). MMP-3 synthesis is tightly controlled in vivo (13,15).…”
Section: Introductionmentioning
confidence: 99%